Familial Erythema Annulare Centrifugum pada Anak Berusia 9 Tahun - Achmad Satya Negara; Endra Yustin Elistasari (MEDICINUS, 2021)
Background: Erythema annulare centrifugum (EAC) is a rare cutaneous disease characterized by erythematous papule which slowly migrates and peripherally enlarges into polycyclic lesion with central clearing that usually involves thigh and legs area. The etiology is unclear, but presumabley related with medication history, infection, malignancy, and stress. The diagnosis of EAC is based on clinical manifestations and histopathological examination. Histopathologically, EAC can be divided into superficial and deep type. Pathognomonic signs include coat sleeve and trailing scale. Symptomatic treatment of EAC may involve topical corticosteroid, topical vitamin D analog, and antihistamine. Case: A 9-year-old boy came with a complaint of erythematous patches on his face and body. Histopathological biopsy showed showed a mild appearance of hyperkeratosis and spongiosis at the epidermis, and perivascular lymphocytic infiltrate at the dermis. Based on these findings, patient was diagnosed with erythema annulare centrifugum. We gave antihistamine and topical corticosteroid to treat his condition. Discussion: Erythema annular centrifugum is a rare skin condition, with most cases is idiopathic. Histopathological biopsy can be used to help establish the diagnosis of EAC. Topical & systemic corticosteroid is the first-line therapy of idiopathic EAC, but administration of empirical therapy using antibiotics or antifungals may also be considered.